2022
DOI: 10.3389/fcell.2021.794912
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, Epigenetics, Cellular Immunology, and Gut Microbiota: Emerging Links With Graves’ Disease

Abstract: Graves’ disease (GD) is a well-known organ-specific autoimmune disease characterized by hyperthyroidism, goiter, and exophthalmos. The incidence of GD is approximately 2.0–3.0% in China and 0.5–2.0% in Western countries. Due to the complex pathogenesis and etiology of GD, current treatment methods have great side effects that seriously endanger human health. Therefore, it is particularly important to understand the pathogenesis of GD. Various studies have shown that genetics, epigenetics, cellular immunology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 135 publications
(171 reference statements)
0
20
0
Order By: Relevance
“…IGFBP4 methylation is increased in CD patients compared to UC patients, and thyroid hormone levels may be associated with the IGF-1/IGFBP system ( 46 , 47 ). Recently, published studies have shown that the imbalance of T-helper 17/regulator T cells induced by epigenetics also plays a vital role in CD ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP4 methylation is increased in CD patients compared to UC patients, and thyroid hormone levels may be associated with the IGF-1/IGFBP system ( 46 , 47 ). Recently, published studies have shown that the imbalance of T-helper 17/regulator T cells induced by epigenetics also plays a vital role in CD ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it significantly suppresses serum levels of anti-cyclic citrullinated protein/peptide (aCCP) antibodies as well as MMP-9 activity [10]. Proper immune balance between T helper cell 17 (Th17) and Tregs is necessary to avoid autoimmune-related immunopathology [39][40][41]. CLT has been revealed to regulate Th17/Treg ratio in the joints of rats with adjuvant arthritis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Among the epigenetic factors associated with AITD, the skewed X-chromosome inactivation (XCI) SNPs of the genes involved in DNA methylation, the DNA methyltransferases (DNMTs) genes, or the methylenetetrahydrofolate reductase (MTHFR) and methionine synthase reductase (MTRR) genes stand out. Other SNPs have also been implicated, such as the immunoregulatory factors ADRB2 (hypermethylated), ICAM1 (hypomethylated), and B3GNT2 (hypermethylated), as well as histone modifications and the impaired expression of noncoding RNAs, among other factors [ 215 , 216 ].…”
Section: Epigenetic Mechanisms In Aitdmentioning
confidence: 99%